2019
DOI: 10.3390/ma12091557
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Loading Comparison between Titanium and Unsintered Hydroxyapatite/Poly-L-Lactide Plate System for Fixation of Mandibular Subcondylar Fractures

Abstract: Osteosynthesis absorbable materials made of uncalcined and unsintered hydroxyapatite (u-HA) particles, poly-l-lactide (PLLA), and u-HA/PLLA are bioresorbable, and these plate systems have feasible bioactive osteoconductive capacities. However, their strength and stability for fixation in mandibular subcondylar fractures remain unclear. This in vitro study aimed to assess the biomechanical strength of u-HA/PLLA bioresorbable plate systems after internal fixation of mandibular subcondylar fractures. Tensile and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…The u-HA/PLLA bioresorbable plates were much weaker than the titanium plates. However, proper plate placement for mandibular subcondylar fracture treatment greatly improved the strength of u-HA/PLLA bioresorbable plates [35].…”
Section: Discussionmentioning
confidence: 99%
“…The u-HA/PLLA bioresorbable plates were much weaker than the titanium plates. However, proper plate placement for mandibular subcondylar fracture treatment greatly improved the strength of u-HA/PLLA bioresorbable plates [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical usefulness of bioresorbable materials has been reported, its insufficient strength is a problem for use in sites where a functional load is applied, such as the jaw. Unlike titanium, bioresorbable materials generally cannot withstand high mechanical loads [ 16 ]. In this study, we first examined the mechanical strength of titanium and u-HA/PLLA bioresorbable screws.…”
Section: Discussionmentioning
confidence: 99%
“…Although the shear strength of u-HA/PLLA was clearly low, as shown in the first experiment, using double-screw fixation generated high strength. This load direction imitates functional load during the lateral movement of the mandible [ 16 , 30 ]. This result suggested that the bioresorbable screw had sufficient strength for a functional load during the lateral exercise for the osteosynthesis of mandibular condylar head fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations